Typhoid epidemiology, diagnostics and the human challenge model. - Darton, T; Blohmke, C; Pollard, A (2014)
PURPOSE OF REVIEW: Infection caused by ingestion of human-restricted Salmonella enterica serovars Typhi and Paratyphi predominantly affects the most impoverished sections of society. In this review, we describe recent advances made in estimating the burden of illness and the important role improved diagnostic tests may have in controlling infection and report the development of a new human challenge model of typhoid infection. RECENT FINDINGS: Typhoid continues to be a major cause of morbidity, particularly in children and young adults in south east Asia, although accurate assessments are still hindered by the lack of reliable surveillance data. Recent reports of high rates of infection in Africa and the dominance of paratyphoid in several geographic areas are of particular concern. Diagnosis of enteric fever remains frustrated by the nonspecific clinical presentation of cases and the lack of test sensitivity. Methods to improve diagnostic accuracy are hindered by the incomplete understanding of immunobiological mechanisms of infection and lack of a suitable animal infection model. SUMMARY: Enteric fever is a major global problem, the burden of which has only partially been recognized. Control strategies utilizing cheap accurate diagnostics and effective vaccines are urgently required, and their development should be accelerated by the use of a human challenge model.